Phylogenetics and historical biogeography of Solanum section Brevantherum (Solanaceae) - Tovar, Juan D.; André, Thiago; Bohs, Lynn A.; Wahlert, Gregory A.; Giacomin, Leandro Lacerda (Molecular Phylogenetics and Evolution, 2021)
Patterns of diversification in Neotropical plants have been studied intensively over the past decades. Most studies have focused on groups that migrated to and radiated into the Neotropics, however, with little focus on understanding diversification patterns in indigenous Neotropical groups. This study focuses on Solanum section Brevantherum Seithe (Solanaceae), a group of Neotropical nightshade shrubs or treelets defined mostly by terminal inflorescences with long peduncles, plurifoliate sympodial units and porrect-stellate, dendritic-echinoid, or lepidote trichomes. We generated sequences from two nuclear (ITS, waxy) and one plastid marker (trnT-F) to infer phylogenetic relationships under Bayesian and Maximum likelihood approaches. We reconstructed a time-calibrated tree to estimate both the ages of main splits and the ancestral ranges of the lineages. Finally, we carried out a biogeographic stochastic mapping (BSM) analysis to determine the main processes driving current distributions of the group. Results show the non-monophyly of the section as previously recognized and the homoplasy of morphological characters traditionally used to circumscribe it. Two main clades that encompass most species formerly recognized in section Brevantherum are recovered and named as the Erianthum and Abutiloides clades. Divergence time estimates suggest that the Erianthum and Abutiloides clades split around 5.7 Mya in the upper Miocene. Two main dispersal events from the Atlantic rainforest are supported in the Erianthum clade: one dispersal to Mesoamerica and a second dispersal to the Northern Andes. Within the Abutiloides clade, cladogenetic events were restricted to the Andean region. Our BSM analysis suggests within-area speciation and range expansion as the main processes shaping the extant distribution of species of both clades. As no putative morphological synapomorphies can yet be assigned to what could correspond to a new circumscription of Solanum section Brevantherum (with the exclusion of Solanum bullatum Vell. and inclusion of S. inelegans Rusby and four species described since the group last revision) we discourage the continued use of what would be an ambiguous sectional nomenclature. © 2021 Elsevier Inc.
Keywords: Dispersal; Evolution; Nightshades; Patterns; South America